PENGARUH INDEPENDENSI, MEKANISME CORPORATE GOVERNANCE DAN KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi Empiris Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2011 – 2015) - Muda Setia Hamid; Nur Solikhah (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2017)
This research aimed to empirically analyze the effect of independence, corporate governance mechanisms (stock institutional ownership percentage, the percentage of stock ownership management, audit committees, independent directors) and quality audit of the integrity of financial report. The population in this research are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) over the period 2011-2015. The sample used in this research are 39 companies to obtain a sample of 195 observation data using purposive sampling. The conclusion is there is no significant effect between independence, percentage of institutional stock ownership, percentage of stock ownership management, audit committee, independent commissioner on the integrity of financial report and significant effect on the integrity of the quality audit of financial report.